Discovery Learning Model as an Effort to Increase Student Interest and Learning Outcomes - Arwaty Arwaty; Mithen Lullulangi (Universitas Negeri Makassar, 2022)
The purpose of this study was to determine the application of the Discovery learning model to increasing student interest in learning and learning outcomes. This type of experimental research involved 40 students of SMA Negeri 11 Tana Toraja. Using observational data collection to assess interest and test questionnaires to measure learning outcomes. The data analysis technique used is descriptive statistical analysis. The results of the study (1) The application of conventional learning models to students has not been able to increase student interest and learning outcomes. 2) The application of the discovery learning model in biology subjects to students can increase student interest in learning and student learning outcomes. This proves that the discovery learning model is a good learning model and can be the teacher's choice to increase student interest in learning and learning outcomes.